Analisis CPO, Asam Fosfat dan Soda Api Sebagai Pengganti Bahan Bakar Minyak (BBM) Mesin Diesel Dengan Variasi Campuran 98%, 1%, 1% Dan 95%, 2%, 3%, dan 95%, 3% 2% Mengunakan Pengujian Kalor - Putra, Muhlas Adi; Gunawan, Yuspian; Hasanudin, La (Teknik Mesin Universitas Halu Oleo, 2020)
Energy needs continue to grow as the industry develops and the world's population grows. The growing need for fuel oil is causing fewer crude inventories. So we did research on Cpo Analysis, Phosphoric Acid And Fire Soda In Lieu of Fuel Oil (Fuel) Diesel Engines With Mixed Variations 98%, 1%, 1% And 95%, 2%, 3%, And 95%, 3% 2% Using Calorific Testing. Go to this study to find out the calorific value and combustion rate of the biodiesel ed. The results of the study in three biodiesel experiments that were most effective for use were shown in the trial to three CPO 95%, 3% posephuric acid and 2% fire soda with a combustion rate of 0.309 gr/min within 30.42 minutes with a final temperature of 57oC. In the three most effective biodiesel experiments to use, three CPO 95%, 3% asamposfat and 2% soda api witha calorific value of 8208.39 cal/gr with a final temperature of 57oC. In the manufacture of biodiesel that affects from the mixture of chemicals as much as soda fire will be better and the less phosphoric acid it will be good. Keywords: Biodiesel, Calorific Value, and Combustion Rate